Thermodynamics of the encapsulation by cyclodextrins - Suporn Charumanee (2018)
Molecular encapsulation on a molecular basis can be performed by cyclodextrins. The inclusion of organic molecules into the interior changes the properties of these molecules, which may be used for a broad variety of applications. The affinity of guest molecules for the cavities of various cyclodextrins depends on the stereochemistry and on the interaction forces of the molecules involved. Calculations of the thermodynamic parameters show that the reaction entropy is highly important for the inclusion reaction. Completely different reaction mechanisms are observed for various types of cyclodextrins as some of these reactions show enthalpy-entropy compensation. Others are supported by the reaction entropy or are even entropically controlled. Protonation and deprotonation reactions contribute significantly to the inclusion reaction, as first of all the solubility of the compounds in water is strongly influenced by the acidity of the solution, and, moreover, all tautomeric forms of the compounds show different affinities to various cyclodextrins. © 2006 Society of Chemical Industry.